Influence of Zn incorporation in CdS: Structural and morphological studies. (July 2015) - Mukherjee, A.; Fu, M.; Mitra, P.
Abstract: In recent years, cadmium zinc sulfide ( Cdx Zn 1− x S ) alloy compounds have been paid much attention in the fields of opto-electronics, particularly in photovoltaic devices. In this report, the structural, morphological and optical properties of C d x Z n 1 − x S films deposited by chemical bath deposition (CBD), which is a very attractive method for low-cost and large-area solar cell applications, has been presented. The as-grown layers were characterized using XRD, EDAX, FESEM, TEM and UV–vis spectrophotometers. Structural characterization by X-ray diffraction and SAED measurement reveals a dominant cubic structure with a minor hexagonal phase for high zinc content films. EDAX analysis shows nearly stoichiometric films with cadmium excess. Close packed and less dissociated surface morphology was observed in the C d x Z n 1 − x S ternary thin films with lower Z n 2 + content than the higher Z n 2 + content one. Agglomeration of nanocrystals for high zinc content films results in enhanced absorption. The mean grain size of C d 0.5 Z n 0.5 S calculated from TEM image is ~15 nm. Optical absorption study exhibits a distinct blue shift in band gap energy with enhancement of zinc content in the film. Highlights: Cd x Zn1− x S thin films by CBD. Influence of Zn incorporation in CdS. Blue shift in band gap with Zn enrichment.